Virtual reality perceptual training can improve the temporal discrimination ability of swinging during softball batting - Nasu, Daiki; Baba, Takamichi; Imamura, Takumi; Yamaguchi, Masumi; Kitanishi, Yoshitake; Kashino, Makio (Frontiers in Sports and Active Living, 2024)
Perception and action uncoupling in fastball sports anticipatory training is often criticized. Nevertheless, perception-only training offers distinct advantages, such as flexibility concerning time, place, and injury limitations. Therefore, the effectiveness of this training approach warrants evaluation. This study developed a virtual reality (VR) training system based on the idea that the two visual pathways in the brain are associated with visual information attributes, rather than perception or action. A key feature of this study's perception-only training was its presentation of not only the opponent's kinematics but also the ball's flight information (the attributes that guide hitting) to train the visual system necessary for real situations. Seventeen female softball batters were assigned to two groups: a training group (N=9) and a control group (N=8). Only the training group underwent the VR anticipatory skill training to discriminate the different ball speeds. Both groups completed a perception test and an action test on the VR during the pre-and post-training periods. The perception test assessed response accuracy (RA) in discriminating ball speed, and the action test assessed the temporal difference in swing onset (delta onset). Comparison of these two outcome variables between groups revealed that perception-only training improved both perceptual and action responses. This study demonstrated the effectiveness of perception-only training and emphasized the need for its thoughtful utilization and design.